2021
DOI: 10.2147/ijgm.s346610
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Application of Systemic Inflammation Response Index and Platelet–Lymphocyte Ratio in Ovarian Malignant Tumors

Abstract: Objective We aimed to evaluate whether the systemic inflammatory response index (SIRI) and platelet lymphocyte ratio (PLR) are associated with ovarian malignancy and their diagnostic value. Design: This retrospective study compared SIRI, PLR, cancer antigen 125 (CA125), cancer antigen 153 (CA153), cancer antigen 199 (CA199), A carcinoma embryonic antigen (CEA) and alpha fetal protein (AFP) of the two groups in Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Sun et al [ 9 ] demonstrated that a high level of SIRI (≥0.89) is an independent predictor of worse prognosis among gallbladder cancer patients. Huang et al [ 33 ] found that SIRI is useful in helping the differentiation of malignant and benign ovarian tumors, while this study did not assess the prognostic value of SIRI among ovarian tumor patients. Moreover, a recent study [ 34 ] investigated the prognostic influence of the SIRI on the survival outcomes of lung cancer patients receiving concurrent chemoradiotherapy and concluded that a high level of SIRI could independently affect the survival outcomes among those patients.…”
Section: Discussionmentioning
confidence: 79%
“…Sun et al [ 9 ] demonstrated that a high level of SIRI (≥0.89) is an independent predictor of worse prognosis among gallbladder cancer patients. Huang et al [ 33 ] found that SIRI is useful in helping the differentiation of malignant and benign ovarian tumors, while this study did not assess the prognostic value of SIRI among ovarian tumor patients. Moreover, a recent study [ 34 ] investigated the prognostic influence of the SIRI on the survival outcomes of lung cancer patients receiving concurrent chemoradiotherapy and concluded that a high level of SIRI could independently affect the survival outcomes among those patients.…”
Section: Discussionmentioning
confidence: 79%
“…In patients with metastatic pancreatic cancer treated with mFOLFIRINOX, an increase in the SIRI (> 2.3) predicted a greater benefit from treatment [ 35 ]. A large number of studies have shown that the SIRI has a certain predictive effect on the prognosis of patients with gastric cancer, head and neck squamous cell carcinoma, renal cell carcinoma, ovarian cancer, and other tumours [ 36 39 ]. However, there are few studies on the SIRI in rectal cancer patients receiving neoadjuvant chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We read this study 1 with great interest. At present, due to the lack of screening and diagnosis methods for ovarian cancer, there is still a lack of early diagnosis of ovarian cancer.…”
Section: Dear Editormentioning
confidence: 99%